#TITLE_ALTERNATIVE# - SYAFITRI (NIM 12206067); Pembimbing: Dr. Ir. Sudjati Rahmat, LINA
Hydraulic fracturing is one of the well stimulation method to improve production from the well. High gas demand causes the oil and gas exploitation in the unconventional reservoir. Needs a very large gas these days causes the oil and gas exploitation began in the reservoir unconventional. Therefore to produce the gas economically, design and optimization of hydraulic fracturing stimulation are needed. NODAL system analysis conducted to optimize hydraulic fracture. It was consider also for hydraulic fracturing design by using two dimensional KGD method.